Enrobing Ceremony for Judges Thomas Harris, Steven Vartabedian, Edward Sarkisian, Jr. and Lawrence Jones at Fresno's Veterans Memorial Auditorium - Watkins, Howard::::::::: (1987)
Superior Court Judge Lawrence Jones in judicial robe speaking at lectern